2010
DOI: 10.1186/1748-717x-5-91
|View full text |Cite
|
Sign up to set email alerts
|

Treatment results for hypopharyngeal cancer by different treatment strategies and its secondary primary- an experience in Taiwan

Abstract: PurposeThe aim of this study was to evaluate treatment results in our hypopharyngeal cancer patients.Patients and MethodsA total of three hundred and ninety five hypopharyngeal cancer patients received radical treatment at our hospital; 96% were male. The majority were habitual smokers (88%), alcohol drinkers (73%) and/or betel quid chewers (51%). All patients received a CT scan or MRI for tumor staging before treatment. The stage distribution was stage I: 2 (0.5%); stage II: 22 (5.6%); stage III: 57 (14.4%) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 33 publications
7
28
0
Order By: Relevance
“…Our findings agree with previous studies that patients with hypopharyngeal SCC had a worse outcome than patients with oropharyngeal SCC [24,32,39,41]. In this study, the tumor location (oropharynx versus hypopharynx) was weakly associated with the 2-year local control rate and showed slightly significant difference between the control and failure group, in which oropharyngeal SCC had better chemoradiation response than hypopharyngeal SCC.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings agree with previous studies that patients with hypopharyngeal SCC had a worse outcome than patients with oropharyngeal SCC [24,32,39,41]. In this study, the tumor location (oropharynx versus hypopharynx) was weakly associated with the 2-year local control rate and showed slightly significant difference between the control and failure group, in which oropharyngeal SCC had better chemoradiation response than hypopharyngeal SCC.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, 20% of patients underwent TPL as the primary treatment, mainly because of thyroid or cricoid cartilage invasion. Similarly, Chang et al, in a study analyzing treatment results for hypopharyngeal cancer in Taiwan, showed that radical surgery was used first in 20.5% of patients [15]. The induction CT response rate of 80% in the present study was comparable to results reported in recent larynx preservation trials [5][6][7].…”
Section: Discussionsupporting
confidence: 91%
“…The oncologic outcomes reported in the present study were comparable to those published in other studies on locally advanced hypopharyngeal cancer [12,13,15]. Five-year OS rates ranging from 25 to 50% are usually published depending on the clinical characteristics of the patients and treatment modalities.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations